A formação continuada nos discursos de professores da educação superior: a experiência da UFPA e do CESUPA - FERNANDES, Roseane do Socorro da Silva Reis (2007)
This is a research developed in the field of the teacher's continuous formation and discusses about the meanings that the teachers which work in the superior education give to the continuous formation and it focalizes the opinions of the teachers that participate in the groups of formation in the Federal University of Pará (UFPa) and in the University Centre of the State of Pará (CESUPA). The empiric material produced based on the documental analysis and the interviews were analysed supported on the national and international bibliography which have a critical perspective about the teacher's work when the authors make a detailed exam about the teacher's profession. This study make reference to the comprehension about how the teachers faces the experience of formation in these two institutions, the effects that the models of the continuous teacher's formation have in their personal and professional development, emphasizing the senses and the interests announced by them. We have evidences that the teachers search for learning when they valorize the access to the formative courses, specially to the contents that can help them on their pedagogic practice. After this study, I could see that the continuous formation is a heterogeneous arena, not unified and have many purposes. We cannot give to the this formation a redemption ideia, imagining that with these courses the teachers will learn to make everything different and correctly, but as an intervention with a critical perspective about the pedagogic practices and that helps to re-construct permanently the personal and professional identity of the teachers in mutual interaction.